SYNTHESIS OF PHOSPHORUS BCNO SILICA WITH NANOCELLULOSE AS CARBON SOURCE FOR WHITE LED APPLICATIONS - Putu Darma Ruswara, I
Lighting is an important aspect of human life. The light can be obtained through various light sources such as lights. White LED is one of the most widely used lights in everyday life. The development of white LEDs is still ongoing today. Initially, white LEDs were obtained from the synthesis of rare earth materials such as Aluminum Garnet Yttrium (YAG) or using the RGB method. Because the synthesis process is not easy and inefficient, a phosphorus BCNO silica is developed as one of the materials to get white LEDs. In this study, phosphorus BCNO silica will be developed using carbon sources from biomass, which are abundant in Indonesia. The elements used to obtain phosphorus for silica BCNO are boron, carbon, nitrogen, and oxygen. Boron is obtained from boric acid and nitrogen compounds obtained from urea compounds. The carbon source used in this study was nanocellulose obtained with biomass mesynthesis. The biomass to be synthesized is pineapple fiber and rice husk. Comparison of molar urea and boric acid in the phosphorus composition of silica BCNO is 20. For nanocellulose the concentration will vary, starting from 0.1%, 1%, 2.5%, and 5%. Nanosilica will be added to the solution with a ratio of 3% wt with a size of 43-54 nm. Silica BCNO phosphorus obtained using nanocellulose from pineapple fiber has a high average illumination at a concentration of 1% while for phosphorus BCNO with nanocellulose from rice husk the average illuminance increases with the addition of nanocellulose concentration in solution. This difference is caused by the biomass used as a carbon source that has different material content. Rice husk has a silica content of 17%. After being synthesized into nanocellulose, the silica remains relatively small in number. Silica will have an effect on the UV lamp flux. The obtained silica phosphorus BCNO is not calcined so that energy use in the synthesis process can be reduced. The UV LED lights obtained have increased illuminance when compared to UV LEDs without a phosphor coating BCNO silica, but the resulting color tends to be blue. Factors that cause the absence of white due to the absence of bleeding red and green light from the material obtained. The illumination results obtained show that phosphorus BCNO silica as an alternative material to be applied to white LEDs can be further developed for further research.